ENGAGEMENT AND CONDUCT OF THE UNDERCOVER INVESTIGATOR - ETHICAL CHALLENGES OF LEGAL SOLUTIONS - Ljubinković, Marija (Glasnik Advokatske komore Vojvodine, 2020)
The challenge of proving the crimes of the 21st century lies largely with the constant progress and improvement of methods and ways of action of the perpetrators, which is especially characteristic of the most serious forms of crime that threaten the security of the state and all its citizens. Therefore, there is a need for specific state action both in the prevention of these crimes and in their repression. They include the use of special evidentiary actions provided by law. As the most complex one of them, in Serbian legislation there is the action of hiring an undercover investigator. The key feature of the undercover investigator's actions is contained in Art. 185, para. 4 of the CPC, which implies that it is prohibited and punishable for an undercover investigator to incite the commission of a criminal offense. However, other legislatures, such as U.S. law, are familiar with the institute of the agent provocateur. The question that arises is related to ethics, but also the efficiency of various legal solutions, and the aim of this research is a kind of scientific explanation of the relationship of both legal solutions to ethics in general, but also to numerous legal institutes that may be in danger in case of provocation. In conducting this research, in addition to analytical-synthetic and inductive-deductive methods, the statistical method also had an important place because a short survey questionnaire was used on the examined body of 82 random respondents.
Keywords: undercover investigator, agent provocateur, special evidentiary actions, ethics, comparative legislation, moral responsibility, legal responsibility